Knowledge and Experience of Teledentistry among urban population of Lahore - A Cross-Sectional Study - Wajiha Alamgir, Uzma Jabbar Khan, Adeel Haider, Palwasha Babar, Ranaa Yousuf (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The specialty of dentistry was being reassembled in its response to Covid-19 pandemic. Teledentistry proved to be a promising way to reach the marginalized population, therefore providing effective substitute of physical dentist-patient interaction with minimal risk of cross infection. Aim: To assess the level of knowledge regarding teledentistry among urban population of Lahore. Moreover it was also focused to analyze the experience and satisfaction of patients regarding the use of virtual dental platforms. Methodology: A cross-sectional study was conducted from April 2022 to June 2022 among 125 general dental patients visiting University Dental Hospital, University of Lahore who have used the virtual dental platforms. The sampling was done with non-probability convenience sampling technique. A self-structured questionnaire with 21 close ended questions was used. Questionnaire was divided into two sections. The first section consisted of 5 questions regarding patient’s demographic data, how did they get to know about teledentistry and for who didthey used teledentistry platform. Results: A total of 125 patients participated in the study, out of which 38(30.4%) were male and 87(69.6%) were female. A large majority 120(96%) of patients were in the age category of 20-40 years. In reference to education, majority of the participants were graduates 107(85.6%). According to our study 14(11.2%) participants wereextremely familiar with the term teledentistry compared to 42(33.6%) who were slightly familiar and only 12(9.6%) were extremely unfamiliar. Regarding familiarity about different platforms of teledentistry (e.g., Marham, Oladoc etc. 30(24%) were moderately familiar 13(10.4%) were extremely familiar and 30(24%) were extremely unfamiliar. About satisfaction, majority 62(49.6%) of people were satisfied with the increasing trend of teledentistry. Conclusion: The majority of the survey participants expressed positive responses towards teledentistry in all domains. This study found high levels of patient satisfaction with virtual consultation.There is a further need to improve the knowledge and promote teledentistry. Keywords: Teledentistry, Telecommunication, Oral healthcare, knowledge, experience